Contribution of Remote Sensing for Estimating the Impact of Environmental Change, in the Detection of Japanese encephalitis Disease in Gorakhpur District, India - , Shipra Verma, R. D. Gupta (Archives of Current Research International, 2015)
It is an important consideration of any area to be distributed spatially. Japanese encephalitis (JE) is a Vector Borne Disease (VBD) that is widespread in Asia. It results in severe illness, death, and hence in economic damage to households. In health planning and management, it is important to demonstrate the land use planning, and water resource planning in order to formulate the vector accumulation around the surroundings. The potential larval habitats of JE were identified using integrated remote sensing and Geographic Information System (GIS) analysis. Remote sensing is a technique to provide data and relate the factors of disease mainly vegetation and water. The objective of study is used remote sensing technique to relate and monitor the predictive area for infectious diseases. Remotely-sensed data have generally been used in two ways, namely (i) for the identification and mapping of land cover associated with host and/or organism habitats, and (ii) for the use of NDWI techniques to find out the vegetation and water content. Land cover classes, vegetated area, and presence of soil surface water content are high in growing seasons and the disease susceptibility also occurs in the areas and seasons. The results represent spatial maps of 2006 and 2009, interrelate the JE disease factors with remote sensing. It is used for depicting the area that significantly predicts the higher spread of disease. In future planning, these spatial maps of two different years appear as a promising and delineating strategy for the further JE disease study.